Turnover Intention in a Conventional Bank: How is it Related to Job Satisfaction, Job Stress, and Hijrah? - Reny Soviana; Hilma Raimona Zadry; Lusi Susanti (Universitas Negeri Padang, 2022)
Every company activity is carried out by human resources, a valuable asset for the company. If a company has competent, loyal and tough employees, then, of course, the company’s progress can be seen more quickly. The turnover phenomenon is one of the problems that are often faced by companies, including those faced by the management of Company XYZ, a branch of banking company in West Sumatra. Thus, it is necessary to know the factors influencing turnover intention, including job satisfaction, job stress, and moving from conventional banks. This study aims to measure and analyze the effect of these three variables on employee turnover intention and analyze the critical factors at Company XYZ. Quantitative research was conducted by distributing questionnaires to the population with 99 respondents. The data analysis technique used is Structural Equation Modeling (SEM) with Smart-PLS software. The study results found that job satisfaction had a negative and insignificant effect on turnover intention. Furthermore, work stress has a positive and significant effect on turnover intention. The last variable is hijrah from conventional banks, a critical factor that positively influences turnover intention with a t-value of 6.350.